KORELASI ANTARA DIMENSI VENA PORTA DENGAN KEKAKUAN HEPAR PADA PASIEN SIROSIS HEPATIS DI CHILD PUGH A - Santoso, Antonius Gunawan; Mubarok, Nala Khodlil; Widyasari, Maya Nuriya; Purnomo, Hery Djagat (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: Liver cirrhosis is an end-stage liver disease characterized by pathologic fibrosis and regenerative nodules with resultant liver dysfunction. The diagnostic hallmark of portal hypertension is slow flow velocities in addition to the increased caliber of the mean portal vein. That is, the diagnosis of portal hypertension requires the measurement of mean portal velocity and portal diameter, and the correlation between cirrhosis and mean portal velocity and port diameter is the correlation between liver cirrhosis and its complications.OBJECTIVE: To analyze the correlation between portal vein dimensions and liver stiffness in patients of Child-Pugh A cirrhosis.METHOD: This study was a cross-sectional study on 30 subjects with Child-Pugh A liver cirrhosis. The subjects of this research are patients who come to the Radiology Department of the Dr. Kariadi Hospital in Semarang for point shear wave elastography and abdominal ultrasound examination from January to December 2022. Spearman test correlation was used for the analysis.RESULT: Spearman test showed no correlation between liver stiffness and portal vein diameter (p=0.250, r= -0.217), liver stiffness and mean portal vein velocity (p=0.883, r= -0.028), and portal vein diameter with mean venous velocity in Child-Pugh A liver cirrhosis (p = 0.979, r = 0.005)